(untitled) (World Science, 2019)
The article presents the results of an analysis of the market for drugs from the group of S07-Beta-blockers, as well as a study of the dynamics of changes in indicators of their socio-economic availability. It was established that during 2015-2019 the number of trade names of drugs increased. In this segment of the market, imported drugs dominate (64.94% -65.91%), as well as single drugs. In addition, there is a significant prevalence of drugs under international names such as C07AB07-Bisoprolol (33.3% of the total assortment of beta-blockers), C07AG02-Carvedilol (19.48%) and C07AB02-Metoprolol (10.83%). Despite all the efforts of the government to implement the «Affordable Drugs» program in 2018, drugs from the C07-Beta blocker group were not available to the country’s population. (D≤1.0). This indicates the need to implement a larger government program aimed at improving the socio- economic availability of antihypertensive drugs in Ukraine.